2007
DOI: 10.1007/s00418-007-0320-8
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic differences between red pulp capillary and sinusoidal endothelia help localizing the open splenic circulation in humans

Abstract: The distribution of capillaries, sinuses and larger vessels was investigated by immunohistology in paraffin sections of 12 adult human spleens using a panel of antibodies. Double staining for CD34 and CD141 (thrombomodulin) revealed that capillary endothelia in the cords of the splenic red pulp and at the surface of follicles were CD34(+)CD141(-), while red pulp sinus endothelia had the phenotype CD34(-)CD141(+). Only in the direct vicinity of splenic follicles did sinus endothelial cells exhibit both antigens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 28 publications
4
24
0
Order By: Relevance
“…SEM of vascular corrosion casts of the human spleen (7) has further confirmed that some of the penicillar arteries, after passing through a splenic follicle, make a hairpin turn and return to the follicle to form bundler arteries. Immunohistochemical studies have focused on the vasculature of the human spleen (11)(12)(13)(14)(15)(16)(17)(18)(19). Steiniger et al performed double staining of serial sections of human spleens for CD34 (a marker for the vascular endothelium) and CD141 (a marker for the sinus en-oxidase activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SEM of vascular corrosion casts of the human spleen (7) has further confirmed that some of the penicillar arteries, after passing through a splenic follicle, make a hairpin turn and return to the follicle to form bundler arteries. Immunohistochemical studies have focused on the vasculature of the human spleen (11)(12)(13)(14)(15)(16)(17)(18)(19). Steiniger et al performed double staining of serial sections of human spleens for CD34 (a marker for the vascular endothelium) and CD141 (a marker for the sinus en-oxidase activity.…”
mentioning
confidence: 99%
“…The sections were pretreated with Immunosaver and 2% normal goat serum, and were incubated with a mouse monoclonal anti-CD34 antibody at a 1 : 200 dilution in PBS overnight at 4°C. Subsequently, sections were washed in PBS, incubated with a biotinylated goat anti-mouse IgG at a 1 : 200 dilution in PBS for one hour, washed in PBS, and incubated with dothelium) and found evidence to support the open theory of splenic circulation (13). They further performed a three-dimensional (3D) reconstruction of serial sections immunostained for lymphocyte makers and CD34, and found that the central artery gave off pulp arteries in the vicinity of the splenic follicle (16).…”
mentioning
confidence: 99%
“…Small arterioles and metarterioles could, however, not be unequivocally distinguished from capillaries because antibodies directed against components of smooth muscle cells did not react with these vessels. In addition, a special type of fibroblasts at the surface of splenic trabeculae, under the splenic capsule and in the adventitia of larger vessels, also expressed CD34 (Steiniger et al 2007). In one individual, a few large white blood cells, which may represent hematopoietic stem cells, inside sinuses were strongly positive (not shown).…”
Section: Cd34 and Cd141 In Human Spleensmentioning
confidence: 99%
“…With both methods, CD34, as detected by mAb QBend10, was primarily found in arteriolar and capillary endothelial cells (Steiniger et al 2007). The staining did not differ in both cell types.…”
Section: Cd34 and Cd141 In Human Spleensmentioning
confidence: 99%
See 1 more Smart Citation